STUDY ON THE OPTIMIZATION OF COLLOID CONCENTRATION IN THE FORMATION OF 2D JANUS ARRAYS OF CITRATE AND 3-MERCAPTOPROPIONIC ACID CAPPER GOLD NANOPARTICLES AS BIOSENSOR PROBES - Reza Fahriyansyah, Muhammad
The development of nanotechnology, particularly the utilization of metal nanoparticles such as gold and silver, has now been applied in the fabrication of nano devices like sensors and optoelectronics. Gold nanoparticle (AuNP)-based plasmonic sensors have been found to possess significantly higher sensitivity compared to other conventional